2013
DOI: 10.1016/j.ejvs.2013.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Initial and Middle-term Results of Treatment for Symptomatic Spontaneous Isolated Dissection of Superior Mesenteric Artery

Abstract: Conservative treatment without anticoagulation can be applied successfully to the patients with symptomatic SIDSMA. Our strategy of restricting ES for these patients who have compression of the true lumen or dissecting aneurysm likely to rupture (and for those with failed conservative treatment) was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 21 publications
0
84
1
1
Order By: Relevance
“…Moreover, multiple lateral branches of the SMA may be occluded by stent placement. 26, 31 Rong et al 15 and Chang et al 33 reported serious complications, including death. Surgeons should be aware of complications if endovascular stent placement is performed.…”
Section: Disclosuresmentioning
confidence: 99%
“…Moreover, multiple lateral branches of the SMA may be occluded by stent placement. 26, 31 Rong et al 15 and Chang et al 33 reported serious complications, including death. Surgeons should be aware of complications if endovascular stent placement is performed.…”
Section: Disclosuresmentioning
confidence: 99%
“…In general, recent first-line therapy has been conservative management, with or without antithrombotic treatment with antiplatelet and anticoagulant therapy to prevent TL occlusion by stabilizing the intimal flap (Figure, Table). [3][4][5][6][7][8][9][10][11] For a subset of patients with persistent symptoms because of critical bowel ischemia or infarction caused by compression of the TL of the SMA or rupture of the dissecting SMA, endovascular treatment (EVT) with stents or open surgical repair (OSR) is indicated without delay. 11 In the current shift towards EVT for aortic or peripheral arterial lesions, 12 EVT predominates.…”
Section: Ogino Hmentioning
confidence: 99%
“…2,6,7 Studies have shown that the false lumen of type II IMAD may readily enlarge. 14 In the present series, conservative treatment was performed in 81.2% of the patients, and 91.1% of these were successfully treated with conservative treatment alone. Only one patient with type III IMAD underwent additional endovascular therapy for recurrent abdominal pain and excessive enlargement of the false lumen.…”
Section: Discussionmentioning
confidence: 62%
“…This could support the speculation, as in several studies, that the length of the dissection was significantly larger in patients with symptomatic IMAD compared with that in asymptomatic patients. 13,14 Vascular stenosis is a critical parameter in IMAD. In a previous study, the true lumen diameter in symptomatic patients was shown to be significantly smaller than that in the asymptomatic patients, 6 which is consistent with the present results (p ¼ .044).…”
Section: Discussionmentioning
confidence: 99%